PAS: An Efficient Privacy-Preserving Multidimensional Aggregation Scheme for Smart Grid - Hui Zhu; Fen Liu; Rong Yan; Hui Li (International Journal of Distributed Sensor Networks)
As a convergence of traditional power system engineering and information technology, smart grid, which can provide convenient environment of operation and management for the power provider, has attracted considerable interest recently. However, the flourish of smart grid is still facing many challenges in data security and privacy preservation. In this paper, we propose an efficient privacy-preserving multidimensional aggregation scheme for smart grid, called PAS. Without disclosing the privacy-sensitive information (e.g., identity and power consumption) of users, the operation center can obtain the number of users and power consumption at each step in different dimensions. Based on an improved Paillier cryptosystem, the operation center can acquire more valid information to regulate the generated energy, and an efficient anonymous authentication scheme is employed to protect the privacy of user's identity from the regional center. Detailed security analysis shows the security and privacy-preserving ability of PAS. In addition, performance evaluations via extensive simulations demonstrate that PAS is implemented with great efficiency for smart grid in terms of computation and communication overhead.